COVERAGE OF THE HISTORY OF GERMAN COLONIES IN VOLYN IN GERMAN-LANGUAGE SOURCES - Суліменко, Олександр (SWorldJournal, 2025)
The purpose of the article is to shed light on the history of German colonies in Volyn on the basis of the German-language sources - newspapers, magazines, articles, memoirs, monographs. The scientific novelty is determined primarily by the involvement of